The Routledge companion to video game studies - Wolf, Mark J. P.; Perron, Bernard (New York, NY Routledge, 2014)
"The number of publications dealing with video game studies has exploded over the course of the last decade, but the field has not yet produced a comprehensive reference work. The Routledge Companion to Video Game Studies, by well-known video game scholars Mark Wolf and Bernard Perron, aims to address the on-going theoretical and methodological development of game studies, providing students, scholars, and game designers with a definitive look at contemporary video game studies. Features include: -comprehensive and interdisciplinary models and approaches for analyzing video games; -new perspectives on video games both as art form and cultural phenomenon; -explorations of technical and creative dimensions of video games; -accounts of the economical, political, social, and cultural dynamics of video games"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Video games; Video games industry -- Social aspects